Experimental study of methane hydrate dissociation in porous media with different thermal conductivities - Li, Xiao-Yan; Wang, Yi; Li, Xiao-Sen; Zhang, Yu; Chen, Zhao-Yang (International Journal of Heat and Mass Transfer, 2019)
Methane hydrate dissociation is an endothermic reaction. Therefore, one of important factors for methane hydrate dissociation is the heat transfer rate. In order to study the heat transfer characteristics of porous media on methane hydrate dissociation, experiments of methane hydrate dissociation using depressurization are conducted in porous media with different thermal conductivities, including quartz sand (0.926 W/(m.K)), white corundum (28.82 W/(m.K)) and silicon carbide (41.9 W/(m.K)). Experimental results show that, during the depressurization stage (DS), the temperature difference among different positions in quartz sand is larger than that in white corundum and silicon carbide. Since the heat transfer rate of quartz sand is smallest among three kinds of sand. A low temperature zone at the center of the reactor is observed in quartz sand compared to white corundum and silicon carbide. During the constant pressure stage (CPS), as the thermal conductivity of porous media increases, the temperature rising rate increases, and the duration of the CPS decreases. The dissociation rate of methane hydrate is controlled by the heat transfer rate of sediments during the CPS. The minimum gas production rate is obtained from the experimental in quartz sand, and the maximum gas production rate is obtained from the experiment in silicon carbide. This result indicates that the dissociation rate of hydrate increased with the increase of the thermal conductivity of porous media. Meanwhile, the overall rate constants (k(overall)) for different runs are calculated to quantify the dissociate rate of methane hydrate during the CPS. As the thermal conductivities of porous media increase, the overall rate constant of methane hydrate dissociation increases. The results of this study are important for understanding the effects of thermal conductivity of porous media on hydrate dissociation in actual field. Furthermore, it can also be used for the validation of numerical simulation in future. (C) 2019 Elsevier Ltd. All rights ...